GAMBARAN TINGKAT PENGETAHUAN WANITA USIA SUBUR TENTANG PEMERIKSAAN PAYUDARA SENDIRI DI DESA MUNDEH TAHUN 2023 - Juliani Waisnawati, Ni Kadek; Erawati, Ni Luh Putu Sri; Widya Ningtyas, Listina Ade (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 3 (2023): Desember 2023DO - 10.24843/ACH.2023.v10.i03.p07, 2023)
ABSTRACT Cancer is an abnormal growth of body tissue cells that turn malignant. Women belong to a high risk group for breast cancer. BSE is an efficient and effective method for early detection of breast cancer. Based on a preliminary study conducted in Mundeh Village in 2021, there were five cases of breast cancer. The purpose of this study was to describe the level of knowledge of women of childbearing age about breast self-examination. This type of research is descriptive research conducted with cross sectional study in March-April 2023 in Mundeh Village. The sampling technique used is probability sampling with random sampling method. The sample is 88 people. Data collection by questionnaire. The results showed that most of the respondents aged >35 years (74.5%) had good knowledge. The majority of WUS with junior high school education (70.0%) have good knowledge and the majority of WUS who work (70.7%) have good knowledge. It is hoped that WUS will be more active in seeking information about breast cancer and balanced with health workers who continue to intensively provide the latest information about breast cancer so that people understand more about the importance of doing BSE from an early age. Keywords: BSE, Knowledge, fertile woman.